STRATEGI KEBIJAKAN PENGEMBANGAN INFRASTRUKTUR BANDARA AHMAD YANI DAN DAMPAKNYA TERHADAP PERTUMBUHAN EKONOMI JAWA TENGAH - Indra Dwi Harjanto; Nenik Woyanti (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2019)
Based on the hypothesis of an empirical study, discussing infrastructure in this case air transportation at Ahmad Yani airport includes one sector that must be intervened by the government to increase economic growth which is expected to reduce various development needs and help to invest in future that can reliably support connectivity between -regional and inter-island in Indonesia This study was conducted to analyze the extent of the role of Ahmad Yani airport infrastructure development in the economy of Central Java Province. The method used is the Input-Output analysis using the Microsoft Excel program and the interview method with the Central Java Bappeda. The data used are secondary data derived from the 2013 Central Java Province Input-Output Table, classification of 88 sectors and primary data derived from interviews with Bappeda Central Java. The analysis carried out consisted of linkage analysis, impact impact analysis, and multiplier analysis, development investment simulation for Ahmad Yani International Airport expansion from APBD of Central Java Bappeda and PT. Angkasa Pura I and SWOT analysis. From the analysis carried out, it can be seen that the building sector that represents the existence of airports in the I-O Table of Central Java Province in 2013 has the ability to increase output demand from other sectors which will be used as input in economic activities, which means that the building sector encourages growth in the upstream sector. Based on the investment simulations carried out, the construction of Ahmad Yani International Airport can increase the output and household income of the community. By considering its contribution to increasing output and income of the community, infrastructure development should be a major concern and priority for the central and regional governments of Central Java Province, especially in development plans to support economic activities in an effort to improve the economy in the medium and long term.